Evaluation of Analgesic activity of Methanolic Extract of Amorphophallus Paeoniifolius Tuber By Tail Flick And Acetic Acid-Induced Writhing Response Method - YADU NANDAN DEY,; SHANKHAJIT DE,; AJOY KUMAR GHOSH, (International Journal of Pharma and Bio Sciences, 2010)
The methanol extract of the tuber of Amorphophallus paeoniifolius was studied for its in-vivo analgesic activity by using the tail-flick method and the acetic acid induced writhing response in mice. The safety of extract in animals was confirmed from the acute toxicity studies. The time course study was performed to find the peak time for the maximum analgesic activity. The effective dose of the extract for analgesic activity was calculated from dose-response curve by using the tail flick and acetic acid induced writhing method. In both of the cases diclofenac sodium was used as standard drug. In both of tail flick method and acetic acid induced writhing response method; the intra-peritoneal administration of methanol extract of Amorphophallus paeoniifolius tubers (250, 500 mg/kg) induced a significant analgesic activity in a dose-dependent manner. The plant may have the phytoconstituents which inhibit cyclooxygenase enzyme or act on central opioid receptors (µ receptors).